Impacts of Precipitating Methods on the Physicochemical, Rheological, and Functional Properties of Borassus aethiopum Mart Fruit Pulp Pectin - Sylvie Assoi; Louise Wicker (Emerging Challenges in Agriculture and Food Science Vol. 5, 2022)
In Africa, the fruits of Borassus aethiopum Mart trees are underutilized and most of them are left to rot in the field. These fruits are rich sources of pectin and thus excellent raw materials for the pectin industry. Since B. aethiopum fruit pectin characteristics are affected by the extraction procedures, it was important to highlight the effects of the precipitating methods on the quality of the isolated pectin. In this study, different precipitating solvents were evaluated, and the characteristics of the final products were determined. Pectin precipitated with isopropanol (IPA), acetone (ACTN), and the 50/50 IPA-ACTN solvents showed great variability in their functional and rheological properties. Isopropanol (IPA) precipitated pectin exhibited the highest (p<0.05) emulsifying activity and the best gel sensorial property. Regardless of the precipitating solvent, high purity pectin with high viscosifying, emulsifying and gelling properties was obtained. Thus, industrial production of pectin from B. aethiopum fruit pulp should be governed by its intended use since extraction and precipitation processes isolate pectin samples with various functionalities.